(untitled) (Annals of Medical Research, 2023)
Aim: Iron deficiency anemia (IDA) is a significant health problem in pregnant women. We aimed to evaluate the effect of gestational IDA and to compare the results of iron therapy in pregnant women. Materials and Methods: This retrospective cohort study of pregnant women in the third trimester analyzed the records of 63 women not taking any iron supplements, 70 women receiving intravenous ferric carboxymaltose therapy (FCM), and 73 pregnant women receiving oral iron therapy. It compared maternal and neonatal outcomes of the three groups. Results: The mean age of the 206 pregnant women included in the study was 29.19±4.34 (19-44; min–max). Only 1% of anemic women received a blood transfusion in the postpartum period. There was no difference between the groups’ mean age and gestational week. The median values of gravida and parity were the same in all 3 groups (Gravida=2, Parity=1). Maternal hemoglobin (Hb) value of the non-iron group was lower than that of the other groups (p<0.001). Although the mothers’ Hb levels at birth were different, the newborns’ Hb values were not affected (p=0.547). Neonatal height and weight were lower in the non-iron group than in the FCM and oral iron groups (p=0.048 and p<0.001, respectively). Neonatal head circumference, 1-minute Apgar, and 5-minute Apgar scores were similar in all three groups. Conclusion: FCM is effective in pregnant women with IDA in late pregnancy and women undergoing this treatment deliver healthier newborns.